A Study of Roundabout Sustainability using Traffic Simulation - A Case Study at Ayer Hitam Signalised Intersection - Asman, Noorazila; Md Rohani, Munzilah; Mohamad Yusri Aman,; Lillian Gungat,; Sitti Asmah Hassan, (International Journal of Sustainable Construction Engineering and Technology, 2023)
Through urban planning and municipal administration, a sustainable city seeks to solve issues of social, environmental, and economic effect. By integrating environmentally friendly options into local infrastructure, many sustainable efforts are made possible. Vehicle emissions from the road traffic have always been considered one of the most significant sources of global issues due to their harmful effects on the environment and human beings. Additionally, it is currently a concern for sustainability, especially in urban areas. This matter has inspired the researchers to simulate various systems to identify factors and provide solutions for the issue of emission. In this study, VISSIM software was utilised to develop a traffic simulation to estimate emissions level at Ayer Hitam’s signalised intersection in reference to the intersection type as an independent factor. The signalised intersection and a roundabout were chosen to represent controlled and uncontrolled intersections. It aimed to compare the difference in emissions level between the signalised intersection and roundabout. The results of this study show that roundabouts are more effective in enhancing traffic flow than signalised intersections in terms of travel time, delay, queue and have 48.59% lower for (CO), (NOx) and (VOC) emission. An improvement in vehicle emissions results from this study indicates that roundabouts have the potential to contribute to a more sustainable transportation system and sustainable city.